Energy efficiency investigation of sun-path tracker systems - Abdellatif Hraich; Ali Haddi; Abdellah El Fadar; Oussama Achkari (EPJ Web of Conferences)
Nowadays, the world is mobilizing to utilize renewable energy sources in nearly every sector to combat pollution. Their design relies on efficiently controlling intermittent energy production through two-way communication between energy generation and consumption, across the entire power grid value chain. The primary objective of this study is to conduct a comparative energy analysis of different Sun Path Trackers. Its offers solutions to optimize photovoltaic energy production through experimentation that incorporates different degrees of freedom photovoltaic panels mounted in mobile bracket and artificial intelligence optimization using stochastic algorithms. The energy data from the photovoltaic panels are stored based via the concept of connected objects (energy internet). This work could enhance the conversion efficiency of the photovoltaic panels by using the sun-tracking technique and the Sun Algorithm Position via Astronomic calculation in the same line. Based on the obtained results, the solution using sun path tracker provides energy yields significantly higher than fixed solar panels.